study of the results of intra vitreal avastin injection on the macular edema after retinal vein occlusion - Bseitoun, Fatema (Latakia University Journal -Medical Sciences Series, 2018)
Aim: discution of the effect of the Bevacizumab(Avastin) on the improvement of visual acuity and macular oedema which intern will improve the quality of patients life. -Study design: Retrospective study -Methods:63eyes with non ischemic central and Branch retinal vein occlusion ( BRVO) between 2011-2015 were studied : VA, IOP, gonioscopy , retinal flourocein angiography, OCT, fundoscopy, before and after injecting(1.25)mg of bevacizumab (Avastin) intravitreal -results: avastin treatment subscribe the regression of the thickness of macula in branch retinal vein occlusion, the percentaged of between( 51.9- 97.1 ) , it improved the visual acuity by percentaged of between ( 82.2 – 83.4) , the visual acuity’s patients above 8/10 to 10/10 by percentaged of 41.93 in situation of BRVO . Non of patients with central retinal vein occlusion arrived to above 7/10 visual acuity. Avastin subscribe the regression of the thickness of the macula in 98.7% in CRVO and 91.4 % in visual acuity improvement. -Conclusion : early treatment with bevacizumab intravitreal after CRVO and BRVO will improve macular oedema and visual acuity . دراسة نتائج حقن الأفاستن على وذمة اللطخة التالية لانسداد الوريد الشبكي الهدف من الدراسة : هو دراسة تأثير الأفاستين على تحسن القدرة البصرية و تراجع وذمة اللطخة مما يؤثر إيجابياً على طبيعة الحياة لدى المريض نمط الدراسة : دراسة راجعة الطرق : دراسة راجعة شملت 63 عين مصابة بانسداد وريد شبكي (بنمطيه الانسداد المركزي الجذعي , والانسداد الفرعي) وتم اختيار (النمط اللا إقفاري . حيث خضع هؤلاء المرضى لـ : فحص قدرة بصرية , قياس ضغط عين , تنظير زاوية البيت الأمامي وقعر العين , تصوير ظليل بالفلورسئين للشبكية , OCT قبل و بعد حقن الأفاستين ضمن الزجاجي بمقدار (1.25mg) . النتائج: العلاج بالأفاستين يساهم في تراجع السماكة لحالة انسداد الوريد الشبكي الفرعي بنسبة تتراوح بين (51.9 – 97.1) % و حسن القدرة البصرية بنسبة تتراوح بين (83.4-82.2)% حيث بلغت نسبة المرضى الذين وصلت القدرة البصرية لديهم حتى 10/10-8/10 في الحالة BRVO إلى 41.93% و لم يصل أي مريض CRVO إلى قدرة بصرية أعلى من 107/, و يساهم في تراجع سماكة اللطخة بنسبة 98.7 % في انسداد الوريد اشبكي المركزي, و بنسبة قدرها 91.4 % في تحسن القدرة البصرية الاستنتاج : في دراستنا تبيّن أن حقن الأفاستين ضمن الزجاجي بشكل مبكر بعد الإصابة بانسداد الوريد الشبكي (المركزي أو الفرعي) يساهم في تحسن القدرة البصرية و تراجع وذمة اللطخة و ذلك بالشكل الفرعي أكثر منه في المركزي .